(untitled) (Journal of the College of Basic Education, 2023)
Many researchers and historians have been interested in studying the history of Al-Ahwaz and the personality of Sheikh Khazal because of its importance in much of modern history. Sheikh Khazal is one of the prominent and important personalities in the Arab region who played an important role in the Arab world and greatly influenced Iraqi society as the most powerful Emir and ruler of Al-Ahwaz region as long as possible.My interest in this research focused on the relations between Iraq and Arabistan and between Mr. Talib Al-Naqeeb and Sheikh Khazal, and I tried to shed light on his relationship with the Ottoman Empire, which was ruling Iraq at the time, from the beginning of his rule until the collapse of the Ottoman Empire in the First World War, and his relationship with the Arab movement in Iraq that it leads. Mr. Talib Al-Naqeeb, and his position on the twentieth revolution and his candidacy to be king of Iraq. The research relied on a number of references, foremost of which is William Theodore Strunk’s book, The Rule of Sheikh Khazal bin Jaber within the Principality of Al-Ahwaz, a study on the British colonial expansion 1897-1925, and he was able to rely on a lot of British documents, and the message of Professor Hussein Hadi Al-Shalah Talib Al-Naqeeb and his role in the modern history of Iraq, and the message of Professor Ahmed Hamdan Al-Tamimi in Basra under the British occupation 1914-1921, as well as a group of books written by Dr. Mustafa Al-Najjar on the history of Al-Ahwaz and the Arabian Gulf.